(untitled) (Jurnal Pembangunan Sosial, 2018)
The counseling competence of a counselor trainer is further enhanced when they are able to perform self-reflection on everything that has been and is being done on the process of counseling operated. This survey was conducted to determine the relation of self-reflection with the three dimension of counseling competence; performing helping skill, managing the counseling process, and handling challenging counseling situations. A total of 100 trainee counselors from four public universities in Malaysia were involved in this study. The instrument used in this study is Self-awareness and Management Strategies (SAMS) Scale to measured the self-reflection, and the Counselor Activity Self- Efficacy Scales (CASES) to measured the counseling competence. Result of the Pearson Product Moment Coefficient indicated there is a significant relationship between self-reflection with counseling competence; performing helping skill and counseling competence;handling challenging counselling A disscussion of the findings are presented and several implications and recommendations for further development of counseling competence of trainee counselors.